Effects of systemic fungal endophytes on the performance of meadow fescue and tall fescue in mixtures with red clover - Dirihan, S. (2015)
A symbiosis between grasses and systemic fungal endophytes exists in both natural and agricultural grassland communities. Our objective was to examine the effects of systemic endophytes on the competitive ability of two agronomically important grass species: meadow fescue [Festuca pratensis (Huds.) syn. Schedonorus pratensis (Huds.) P. Beauv] and tall fescue [Festuca arundinacea (Schreb.) syn. Schedonorus phoenix (Scop.)]. Plants of meadow and tall fescue were grown for 48 days in replacement series of interspecific mixture with a legume (red clover, Trifolium pratense L.) in different nutrient environments in a greenhouse. Neither of the grass species gained endophyte-promoted competitive advantage over red clover in grass–clover mixtures. Endophyte infection increased the growth of meadow fescue monocultures by 89% compared to endophyte-free monocultures in high-nutrient soils, but plant competition or the cost of endophyte infection to the meadow fescue decreased the yield in resource-limited conditions. On average, endophyte-infected and endophyte-free meadow fescues produced 0·15 and 0·17 g, and 0·14 and 0·14 g dry biomass per plant in mixtures with red clover in high- and low-nutrient soils respectively. In contrast to meadow fescue, endophyte-promoted growth of tall fescue monocultures was not detected. Endophyte-infected and endophyte-free tall fescue monocultures produced 0·76 and 0·95 g biomass per pot, respectively, in the high-nutrient environment. Endophyte infection can increase the performance of the host grass, but the positive effects depend on the host species, the species composition and soil nutrient availability.